2010
DOI: 10.1097/hjh.0b013e32833e4149
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor attenuates renal fibrosis through TGF-β1 suppression by apoptosis of myofibroblasts

Abstract: The present study demonstrates that the increase in metalloproteinases through FAK-ERK signaling by HGF promotes myofibroblast apoptosis. Activation of metalloproteinases by HGF in the fibrotic kidney might be considered to attenuate the progression of CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
0
47
0
2
Order By: Relevance
“…17 In addition, our recent study demonstrated that HGF induced apoptosis of myofibroblasts, associated with an increase in MMPs expression and a decrease in ECM, potentially because of inhibition of TGF-␤1 signaling. 5,18,19 In addition to these known mechanisms, the present study suggests a novel pathway through the PI3K-Akt/PTEN pathway. HGF plays the role of antiapoptotic effect, mediating the activation of Akt/ PI3K pathway.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…17 In addition, our recent study demonstrated that HGF induced apoptosis of myofibroblasts, associated with an increase in MMPs expression and a decrease in ECM, potentially because of inhibition of TGF-␤1 signaling. 5,18,19 In addition to these known mechanisms, the present study suggests a novel pathway through the PI3K-Akt/PTEN pathway. HGF plays the role of antiapoptotic effect, mediating the activation of Akt/ PI3K pathway.…”
Section: Discussionmentioning
confidence: 61%
“…5 As shown in Figure S1 (available in the online Data Supplement), TGF-␤1 significantly stimulated the expression of AT 1 R mRNA in a time-dependent manner from 1 to 24 hours (PϽ0.01). In contrast, Ang II stimulation alone did not change AT 1 R mRNA expression ( Figure 1A).…”
Section: Role Of Phosphatase and Tensin Homolog Deleted On Chromosommentioning
confidence: 85%
See 3 more Smart Citations